2015
DOI: 10.1002/pssb.201451612
|View full text |Cite
|
Sign up to set email alerts
|

Nanorippling of ion irradiated GaAs (001) surface near the sputter‐threshold energy

Abstract: Ripple formation driven by Ehrlich-Schwoebel barrier is evidenced for normal incidence 30 eV Ar þ bombardment of GaAs (001) surface at elevated target temperature. The pattern follows the twofold symmetry of the bombarded crystal surface. The ridges of the ripples are found to align along the h1 10i direction. The results are described by a non-linear continuum equation based on biased diffusion of adspecies created by ion impact. Ripple topography on ion bombarded GaAs (001) surface: AFM image (left panel) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 39 publications
(47 reference statements)
2
14
0
Order By: Relevance
“…The remarkable work of Ou et al [27] on hot Ge by 1 keV Ar + sputtering illustrates the formation of ES barrier driven dense arrays of crystalline alternating mounds and pits, resembling homoepitaxial growth of checkerboard structure as obtained in molecular beam epitaxy (MBE) [32]. In our earlier work [28], we also demonstrated the similar kind of pattern formation through the Ar + sputtering near the sputterthreshold energy ~ 30 eV. Since both the investigations were done at normal ion beam incidence, it highly motivates us to extend the pattern formation study at offnormal angle of incidences, especially at grazing incidence angles, in order to realize 5 whether such diffusion-bias-generated instability can influence the morphological evolution at grazing incidence too or some other physical phenomena takes over.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…The remarkable work of Ou et al [27] on hot Ge by 1 keV Ar + sputtering illustrates the formation of ES barrier driven dense arrays of crystalline alternating mounds and pits, resembling homoepitaxial growth of checkerboard structure as obtained in molecular beam epitaxy (MBE) [32]. In our earlier work [28], we also demonstrated the similar kind of pattern formation through the Ar + sputtering near the sputterthreshold energy ~ 30 eV. Since both the investigations were done at normal ion beam incidence, it highly motivates us to extend the pattern formation study at offnormal angle of incidences, especially at grazing incidence angles, in order to realize 5 whether such diffusion-bias-generated instability can influence the morphological evolution at grazing incidence too or some other physical phenomena takes over.…”
Section: Introductionmentioning
confidence: 59%
“…Recently, the ES barrier induced pattern formation on Ge crystal surface by means of IBS at high temperature attracts considerable attention [27][28][29][30][31]. The remarkable work of Ou et al [27] on hot Ge by 1 keV Ar + sputtering illustrates the formation of ES barrier driven dense arrays of crystalline alternating mounds and pits, resembling homoepitaxial growth of checkerboard structure as obtained in molecular beam epitaxy (MBE) [32].…”
Section: Introductionmentioning
confidence: 98%
“…[23,24] even directly state that MD simulations are not suited for studying the surface rippling due to time and size limitations. However, in recent experiments [15,[25][26][27], it was demonstrated that the 30 eV Ar ion irradiation caused the ripple formation on the surface of amorphous Si as well. In the current work, we gain new insights on the process of ripple formation due to a unique combination of a recently developed speedup scheme for MD simulation [28] to simulate tens of thousands of ion impacts on the same surface, with consideration of the new experimental condition of very low ion energy-induced ripples.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonically cleaned 1×1 cm 2 p-type single crystal Si(100) wafers are irradiated by 500 eV Ar + ions at incidence angle 65 • (with respect to surface normal) in a broad beam high current ion beam system (M/s Roth & Rau Microsystems GmbH, Germany) [16]. An inductively coupled RF plasma discharge ion source having threegrid graphite optics system is employed to extract homogeneous ion beam of diameter 3 cm.…”
Section: Methodsmentioning
confidence: 99%